A highly efficient flocculant for graphene oxide recycling and its applications. (29th November 2017) - Luan, Ruiying; Pan, Hui; Ma, Yuning; Mao, Lin; Li, Yao; Wang, Dawei; Zhang, Di; Zhu, Shenmin
Abstract: In this study, we found a novel and efficient way of recycling graphene oxide (GO) by adding ZnO colloid into the GO solution. GO flocculates immediately when mixed with ZnO colloids. Interestingly, the flocculation would disappear and disperse homogeneously in solution if a certain amount of HCl is added. The study offers a solution to recover and reuse GO throughout its production procedures. More importantly, in the obtained reduced GO/ZnO (rGO/ZnO) flocculant, ZnO nanorods are observed self-assembled into an ordered structure in between the rGO sheets. This prevents the rGO sheets from re-stacking and facilitates the movement of the electrolyte into ZnO if the prepared rGO/ZnO is used as an electrode for supercapacitor. Electrochemical measurements have proved that the rGO/ZnO composite with a weight ratio of 1:1 exhibits a gravimetric specific capacitance of 175 F g −1 and the rGO/ZnO electrode maintains 89.6% of the initial capacitance after 5000 cycles of uses.